State autonomy and educational policy: from individual choice to social demand - Post, David (1987)
​Past studies of educational policy in Latin America assume unlimited power and autonomy by the state to restructure social welfare services. These approaches oversimplify a more complex reality, this investigation shows. In this article the foundation of the social demand for university education is examined at its origin, in the individual participants in the process: in the decisions by secondary school graduates. Economic considerations are not the only factors on which students base their future plans, it is discovered. For males, however, especially males within a midrange of family income, these economic considerations are important factors in the decision process. These students' beliefs about the benefit of university education is determined partly by their access to information, it is seen. Access to information results in lower estimations of university salaries. If educational expansion continues in Peru at the rates prevalent in the pre-1984 period, it is concluded, then the education system may contain within it the seeds of its destruction.